Exploring resistance mechanisms of HCV NS3/4A protease mutations to MK5172: insight from molecular dynamics simulations and free energy calculations1. Issue 9 (11th September 2015) - Guan, Yan; Sun, Huiyong; Pan, Peichen; Li, Youyong; Li, Dan; Hou, Tingjun
<x xml:space="preserve">Abstract</x> Mutations at a number of key positions (Ala156, Asp168 and Arg155) of the HCV NS3/4A protease can induce medium to high resistance to MK5172.